Engineering active sites in ternary CeO2-CuO-Mn3O4 heterointerface embedded in reduced graphene oxide for boosting water splitting activity - Sahar Jafari; Zohreh Shaghaghi (Scientific Reports)
Abstract The rational design of highly efficient and stable bifunctional catalysts for overall water splitting is vitally important. In this study, to increase the active catalytic sites of CeO2 for electrochemical water splitting, a ternary CeO2-CuO-Mn3O4 heterostructure, synthesized by coprecipitation method, is loaded on reduced graphene oxide (rGO) nanosheets in different amounts to produce CeO2-CuO-Mn3O4@rGO nanocomposites. It is found that CeO2-CuO-Mn3O4@rGO nanocomposites show higher electrocatalytic activity than unsupported samples, and the best activity is observed when the wieght ratio of CeO2-CuO-Mn3O4 is three times that of rGO. The CeO2-CuO-Mn3O4@rGO(3:1) requires low overpotentials of 130 and 270 mV for hydrogen and oxygen evolution reactions (HER and OER) at a current density of 10 mA cm−2. Furthermore, this material demonstrates a large electrochemically active surface area, low charge transfer resistance, suitable kintics, and high long-term stability for both OER and HER. Additionally, when CeO2-CuO-Mn3O4@rGO(3:1) is used as self-supported electrodes for the overall water splitting reaction, a low cell voltage of 1.68 V is obtained. This superior performance is due to: (i) active multi-metal sites that produce strong synergistic effects; (ii) the high conductivity of rGO, which faciliate favorable electron transfer; and (iii) the homogenous anchoring of CeO2-CuO-Mn3O4 on rGO, which increases the number of active sites available on the catalyst surface.